2012
DOI: 10.1002/met.1339
|View full text |Cite
|
Sign up to set email alerts
|

Early warnings of extreme winds using the ECMWF Extreme Forecast Index

Abstract: ABSTRACT:The European FP7 SafeWind Project aims at developing research towards a European vision of wind power forecasting, which requires advanced meteorological support concerning extreme wind events. This study is focused mainly on early warnings of extreme winds in the early medium-range. Three synoptic stations (airports) of North Germany (Bremen, Hamburg and Hannover) were considered for the construction of time series of daily maximum wind speeds. All daily wind extremes were found to be linked to very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…Similarly, a better performance for Anatol than for the relatively smaller storms Lothar and Martin was previously noted by Buizza and Hollingsworth (2002) in the operational ECMWF ensemble forecast. However, neither this better performance nor differences between the predictability of specific storms found by other authors using the EFI (Lalaurette, 2003;Petroliagis and Pinson, 2014;Boisserie et al, 2016) are confirmed here. This suggests a sensitivity to the ensemble prediction system and to the type and region of the reference data used for their validation, which vary from study to study.…”
Section: Efi and Sot For The 25 Severe Stormscontrasting
confidence: 97%
See 4 more Smart Citations
“…Similarly, a better performance for Anatol than for the relatively smaller storms Lothar and Martin was previously noted by Buizza and Hollingsworth (2002) in the operational ECMWF ensemble forecast. However, neither this better performance nor differences between the predictability of specific storms found by other authors using the EFI (Lalaurette, 2003;Petroliagis and Pinson, 2014;Boisserie et al, 2016) are confirmed here. This suggests a sensitivity to the ensemble prediction system and to the type and region of the reference data used for their validation, which vary from study to study.…”
Section: Efi and Sot For The 25 Severe Stormscontrasting
confidence: 97%
“…This suggests a potential for warnings but with possible false alarms, as already noted by Lalaurette (2003). The use of EFI and SOT thus requires an appropriate balance between hit and false alarm rates (Petroliagis and Pinson, 2014;Boisserie et al, 2016).…”
Section: Extreme Forecast Index (Efi) and Shift Of Tails (Sot)mentioning
confidence: 82%
See 3 more Smart Citations